2020
DOI: 10.1007/s13280-019-01311-w
|View full text |Cite
|
Sign up to set email alerts
|

Developing a circumpolar programme for the monitoring of Arctic terrestrial biodiversity

Abstract: The Arctic is undergoing biological and environmental changes, and a coordinated effort to monitor is critical to detect these changes. The Circumpolar Biodiversity Monitoring Programme (CBMP) of the Arctic Council biodiversity working group, Conservation of Arctic Flora and Fauna (CAFF), has developed pan-Arctic biodiversity monitoring plans that aims to improve the ability to detect and report on long-term changes. Whilst introducing this special issue, this paper also presents the making of the terrestrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Indeed, a review of experimental warming studies and long-term monitoring in the Arctic showed that no change in plant abundance was the most common response (Bjorkman et al 2020). High Arctic, sensu Christensen et al (2020), vegetation abundance is characterized by no or weak trends in relation to experimental warming and ambient rising temperatures (Hudson and Henry 2010;Prach et al 2010;Elmendorf et al 2012a). This heterogeneity in vegetation responses to warming challenges monitoring to strike a balance between ecosystem-specific understanding and general understanding of tundra vegetation changes that can be applied more universally.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a review of experimental warming studies and long-term monitoring in the Arctic showed that no change in plant abundance was the most common response (Bjorkman et al 2020). High Arctic, sensu Christensen et al (2020), vegetation abundance is characterized by no or weak trends in relation to experimental warming and ambient rising temperatures (Hudson and Henry 2010;Prach et al 2010;Elmendorf et al 2012a). This heterogeneity in vegetation responses to warming challenges monitoring to strike a balance between ecosystem-specific understanding and general understanding of tundra vegetation changes that can be applied more universally.…”
Section: Introductionmentioning
confidence: 99%
“…Two FEC attributes identified as essential by the Circumpolar Biodiversity Monitoring Programme (Christensen et al 2020) were quantified in this study, namely diversity (alpha diversity, rare species, community composition) and abundance (percent cover). Along with voucher specimens representative of plot vegetation species and deposited at the Louis-Marie Herbarium (Quebec City, Quebec, Canada) and at the Canadian Museum of Nature Herbarium (Ottawa, Ontario, Canada) (Desjardins et al 2021a), we archived in Nordicana D (Desjardins et al 2021b) the complete floristic database of 264 georeferenced and photographed vegetation plots, including 50 plots with permanently marked quadrats.…”
Section: Monitoringmentioning
confidence: 99%
“…In addition, experiments were short term and conducted at few sites (Elmendorf et al 2012). In this context, establishing baselines and implementing monitoring schemes to track the responses of Arctic plant communities to climate change are critical (Mihoub et al 2017;Christensen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations